UNJUK KERJA LAYANAN BEST EFFORT ARAH DOWNLINK TERKAIT POSISI USER EQUIPMENT DAN POLA PAKAI-ULANG FREKUENSI - , PRASETYAN NUR FIRDAUS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Capacity is a very important factor in broadband wireless access networks like LTE. But the major factor limiting the capacity is interference originating from neighboring cells, namely intercell interference. Intercell interference (ICI) occurs because of the influence of the same frequency band working in the neighboring cells. To minimize the effect of intercell interference, a technique called frequency reuse is used. The aim of this study is to evaluate the effect of ICI on cell-edge users in three-cells LTE system model. In the simulations, best effort service quality was analyzed as an indicator of intercell interference. By using the conventional reuse systems, such as sistems reuse three and four, the simulation results showed that ICI could be minimized proven by increasing SINR value of 206% and MCS values of 152% for cell-edge user on the channels. Finally the metrics of best effort traffic such as PLR generated through frequency reuse three showed better results than reuse one, proven that cell-edge users experience almost 0% for PLR. But the use of frequency reuse three actually resulted in increasingly smaller network capacity in each cell, so that the value of goodput drop about 50% for each user.